Racial/Ethnic Differences in Framingham Risk Score in an NHANES Cohort - Ashley, Farokhrouz; Rodney, G. Bowden; Kathleen, A. Richardson; Tanvir, Ahmed; Jaimala, Kishore (Journal of Preventive Medicine And Care, 2024)
Objective Studies assessing the risk of developing CVD between different racial groups in the United States have reached varying conclusions. The purpose of this study was to identify risk for CVD using the Framingham Risk Score (FRS) between racial/ethnic groups. A secondary aim of this study was to compare risk for CVD based on SES status/poverty ratio. Methods A cross-sectional data analysis was conducted using the 2015-2020 NHANES datasets using individuals aged 18 to 79 years. Sample weights were assigned by NHANES researchers to each participant allowing researchers to generalize results to all non-institutionalized US civilians. Results Mexican Americans (MA) had the lowest average FRS and significantly lower CVD risk than all other racial groups, except NH Asian. NH Asians had the second lowest FRS and significantly lower risk than NH Blacks and NH Whites, but their risk was similar to other Hispanic or the other/multi-racial groups. NH Blacks showed no significant difference in FRS compared to NH Whites, other Hispanic, and other/multi-racial groups. NH Whites were not statistically different from other Hispanic or other/multi-racial groups. Other Hispanic and multi-racial groups did not exhibit statistically significant differences. Overall, Mexican Americans had the lowest FRS whereas NH Whites had the highest. Conclusions NH whites demonstrated the highest CVD risk according to FRS, as the oldest racial/ethnic group in the cohort. SES did not consistently predict FRS differences between racial/ethnic groups. These findings suggest a need to further explore FRS as a means of identifying individuals who are at high risk of developing CVD.
Keywords: Framingham Risk Score; Cardiovascular Disease; Socio Economic Status; Racial/Ethnic